2000
DOI: 10.1097/00000374-200008000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol Reinforcement in Nondeprived Mice: Effects of Abstinence and Naltrexone

Abstract: Ethanol appears to serve as a reinforcer for non-food-deprived or non-water-deprived B6 mice. Its reinforcing effects are increased by forced abstinence after chronic exposure and are decreased by naltrexone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 34 publications
2
30
0
Order By: Relevance
“…Instrumental response training was conducted with modifications to previously described procedures [23]. Mice were initially trained to consume a 0.2% w/v saccharin solution (0.2S) from a retractable sipper during two 20-min trials per day for 7 days.…”
Section: Sipper and Lever Acquisition Training Phasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Instrumental response training was conducted with modifications to previously described procedures [23]. Mice were initially trained to consume a 0.2% w/v saccharin solution (0.2S) from a retractable sipper during two 20-min trials per day for 7 days.…”
Section: Sipper and Lever Acquisition Training Phasesmentioning
confidence: 99%
“…A modified saccharin fading procedure was used to initiate ethanol self-administration [23,35]. Briefly, the ethanol concentration was increased within the 0.2S solution [for two sessions each at 0.2% saccharin/3% ethanol (0.2S/3E), 0.2S/6E, 0.2S/9E, and 0.2S/12E], and then saccharin was subsequently faded out in a step-wise manner to yield a 10% v/v ethanol (10E) solution [for 5 sessions each at 0.1S/12E, 0.05S/12E, 0.025S/12E, 0.01S/12E, and then 10E].…”
Section: Saccharin Fading Procedures and Reinforcement Schedule Manipumentioning
confidence: 99%
“…A modified saccharin fading procedure was utilized to initiate ethanol self-administration (Czachowski et al, 2001;Middaugh et al, 2000;Samson, 1986). Throughout saccharin fading, mice were maintained on a FR1 reinforcement schedule for 15-sec sipper access periods during 30-min sessions.…”
Section: Saccharin Fading Procedures and Reinforcement Schedule Manipumentioning
confidence: 99%
“…Although the reinforcing effects of ethanol have been successfully demonstrated when the drug is continuously available (Besheer et al, 2004;Hodge et al, 2006;Olive et al, 2000;Risinger et al, 1998Risinger et al, ,1999, data evaluating ethanol reinforcement in mice under a limited access condition is less well studied. Studies with mice responding on a fixed ratio 1 (FR1) (Middaugh et al 2000;Roberts et al 2000) or FR3 (Tsiang and Janak, 2006) reinforcement schedule reported ethanol intake approximating 0.5 g/kg, which correspond to values in rats responding on a FR schedule (e.g., Samson, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…When mice and rats have limited access to an ethanol solution with either 2-bottle choice (e.g., Finn et al, 2004;Ford et al, 2005;Grahame et al, 1999;Li et al, 1993;McBride and Li, 1998) or operant (e.g., Backstrom and Hyytia¨2005; Czachowski et al, 2002;Elmer et al, 1987;Funk et al, 2005;Middaugh et al, 2000;O'Dell et al, 2005;Risinger et al, 1998;Roberts et al, 2000;Tsiang and Janak, 2006) procedures, they can reliably selfadminister doses of alcohol that are believed to be pharmacologically active.…”
mentioning
confidence: 99%